2021
DOI: 10.31557/apjcp.2021.22.10.3165
|View full text |Cite
|
Sign up to set email alerts
|

Association between Early Menopause, Gynecological Cancer, and Tobacco Smoking: A Cross-Sectional Study

Abstract: Background: The rates of smoking among women are rising. Previous studies have shown that smoking is associated with early menopause. However, the association of gynecological cancer, including breast and cervical cancer, with early menopause and smoking, remains unclear. Therefore, this study aimed to determine the association between smoking and early menopause, breast cancer, and cervical cancer. Methods: This cross-sectional study used data from the Korean National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In a study, it was shown that education has a significant and inverse relationship with early menopause, which means that by increasing the level of education, the rate of early menopause decreases [ 26 ]. In two studies conducted in Korea, the prevalence of POI was significantly higher in the people with lower household incomes, and lower education levels [ 15 , 29 ]. The observed inconsistency can be in terms of cultural differences, and the level of access to health services.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it was shown that education has a significant and inverse relationship with early menopause, which means that by increasing the level of education, the rate of early menopause decreases [ 26 ]. In two studies conducted in Korea, the prevalence of POI was significantly higher in the people with lower household incomes, and lower education levels [ 15 , 29 ]. The observed inconsistency can be in terms of cultural differences, and the level of access to health services.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these variables were also used for model construction. Although the influence of menopause status and TZ type on the development of HSIL+ is not consistent, these variables play important roles in colposcopy practice and are recommended by experts to be included in the model [ 6 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…Otros factores de riesgo mencionan el tabaquismo, índice bajo de masa corporal; factores relacionados a la vida temprana y ambientales que incluyen abuso sexual en infancia y adolescencia, divorcio de padres, aunque se deben realizar más estudios [6,7,17]. Con respecto al riesgo de desarrollar cáncer ginecológico en pacientes que han tenido menopausia precoz, estudios han señalado que no hay relación entre el cáncer cérvico uterino y la menopausia prematura, y con respecto al cáncer de mama, no encontró asociación con un mayor riesgo en pacientes que alguna vez fueron fumadoras [19] Las consecuencias de la IOP y menopausia prematura pueden incluir aparición temprana de síntomas vasomotores, alteraciones del estado de ánimo, disfunción sexual y síndrome genitourinario de la menopausia; alteraciones de la fertilidad; y otras a largo plazo como hipercolesterolemia, disfunción cardiovascular, disminución de la densidad mineral ósea, insulino resistencia, síndrome metabólico, alteraciones de la función cognitiva [1,12,15].…”
Section: Desarrollo Y Discusiónunclassified